2017
DOI: 10.12932/ap0879
|View full text |Cite
|
Sign up to set email alerts
|

Urinary cysteinyl leukotriene E4 level and therapeutic response to montelukast in children with mild obstructive sleep apnea

Abstract: We found the association between ULTE4 and therapeutic response to monteleukast. The uLTE₄ level of ≥ 1,457 pg/mg creatinine could predict the therapeutic response to montelukast in children who had ATH and mild OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Overall, measurement of uLTE 4 is a sensitive and noninvasive method of assaying total body production of CysLTs and is a useful biomarker of exposure to atopic and nonatopic asthma triggers [47,167], recent asthma exacerbations [168], AERD [166,169], early development of childhood atopy [170,171], and obstructive sleep apnea [172,173]; it is also useful for predicting susceptibility to LT receptor antagonists [174,175,176].…”
Section: Urinary Lte4 As a Biomarker Of Allergic Diseasementioning
confidence: 99%
“…Overall, measurement of uLTE 4 is a sensitive and noninvasive method of assaying total body production of CysLTs and is a useful biomarker of exposure to atopic and nonatopic asthma triggers [47,167], recent asthma exacerbations [168], AERD [166,169], early development of childhood atopy [170,171], and obstructive sleep apnea [172,173]; it is also useful for predicting susceptibility to LT receptor antagonists [174,175,176].…”
Section: Urinary Lte4 As a Biomarker Of Allergic Diseasementioning
confidence: 99%
“…Baseline tonsillar hypertrophy and weight gain are predictors of disease progression. 41 In the management of this category of childhood OSA, parents may therefore opt for less invasive intervention such as nasal corticosteroids, 43 leukotriene receptor antagonist 44 and myofunctional therapy. 45 More non-surgical interventional studies for mild childhood OSA are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary cysteinyl leukotrienes (cysLTs) can be used as predictors of the efficacy of montelukast. Several studies demonstrated the positive correlation between OSA severity and cysLT levels [64,66]. Sunkonkit et al reported higher urinary cysLT levels in subjects who responded to montelukast therapy compared to non-responders [66].…”
Section: Leukotriene Receptor Antagonists (Ltra)mentioning
confidence: 99%
“…Several studies demonstrated the positive correlation between OSA severity and cysLT levels [64,66]. Sunkonkit et al reported higher urinary cysLT levels in subjects who responded to montelukast therapy compared to non-responders [66]. Although there are no precise reference values, the authors found that the values of urinary cysLTs E4 (the major urinary metabolite of cysLTs) >1.457 pg/mg creatinine could have a very high specificity and sensitivity in predicting the therapeutic response to montelukast [64].…”
Section: Leukotriene Receptor Antagonists (Ltra)mentioning
confidence: 99%